Supporting ethical practice in community-engaged research with 4R: Respond, Record, Reflect, and Revise - Chou, Tommy (Ethics Behav, 2019)
Efforts towards adaptation, dissemination, and implementation of culturally robust, evidence-informed mental healthcare rely on community-engaged research (CEnR). Academic-community partnerships help bring science to service for vulnerable and historically disenfranchised populations (e.g., communities of color and those characterized by poverty). A growing literature supports the development of a framework of ethics for CEnR. This article examines ethical tensions in the context of the American Psychological Association Ethics Code General Principles – Beneficence and Nonmaleficence; Fidelity and Responsibility; Integrity; Justice; and Respect for People’s Rights and Dignity – and presents the 4R action plan to support application of APA guidelines to academic-community partnership with youth-serving organizations.